Open Organizational Climate As An OrganizationalCommunication Strategy Of Pt. Utero Kreatif Indonesia In EffortsTo Improve Employee Productivity - Irfani Zukhrufillah; Untung, Mohammad; Sukma, Ferry Indra (International Journal of Multidisciplinary Applied and Science Research, 2024)
This study analyzes how an open organizational climate is used as a communication strategyto enhance employee productivity at PT. Utero Kreatif Indonesia. Using a qualitative case studyapproach, data were collected from in-depth interviews, observations, and documents. Findingsshow the strategy blends formal channels (like weekly meetings) with dominant informal ones(e.g., casual chats and WhatsApp). A communicative and supportive leadership style fosteredresponsibility and emotional attachment among employees. However, subtle hierarchies basedon seniority and ambiguous reward systems were key barriers, limiting genuine participationand motivation. The study concludes that an open climate acts as a communication metastrategy, indirectly boosting productivity by promoting psychological safety, role clarity, andrecognition. Success depends on balancing formal communication with authentic informaldialogue while addressing hidden cultural obstacles. This research adds to the literature byintegrating organizational climate theory with communication strategy in an Indonesiancreative company context.